Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Lou, Song-mei (J Zhejiang Univ Sci B, 2019)
Common bile duct (CBD) stones are a frequent problem in Chinese populations, and their incidence is particularly high in certain areas (Wang et al., 2013). In recent years, laparoscopic common bile duct exploration (LCBDE) and endoscopic retrograde cholangiopancreatography (ERCP) have been the main surgical procedures for CBD stones, although each has different advantages and disadvantages in the treatment of choledocholithiasis (Loor et al., 2017; Zhou et al., 2017). For patients with large stones, a dilated CBD, especially concurrent gallstones, LCBDE is the preferred and most economical minimally invasive procedure (Koc et al., 2013). However, a T-tube is often placed during LCBDE to prevent postoperative bile leakage; this is associated with problems such as bile loss, electrolyte disturbance, and decreased gastric intake (Martin et al., 1998). In addition, the T-tube usually must remain in place for more than a month, during which time the patient’s quality of life is seriously compromised. Many skilled surgeons currently perform primary closure of the CBD following LCBDE, which effectively speeds up rehabilitation (Hua et al., 2015). However, even in sophisticated medical centers, the incidence of postoperative bile leakage still reaches ≥10% (Liu et al., 2017). Especially for a beginner, bile leakage remains a key problem (Kemp Bohan et al., 2017). Therefore, a safe and effective minimally invasive surgical approach to preventing bile leakage during primary closure of the CBD after LCBDE is still urgently needed.